Carbon nitride photocatalysts - Zhang, J.; Sun, Hongqi (2018)
© 2018 Elsevier Ltd All rights reserved. Photocatalysis processes for producing alternative and sustainable energy through hydrogen evolution and CO2 reduction have secured a prominent position among all the renewable energy technologies. The emerging carbon-based photocatalyst, namely graphitic carbon nitride (g-C3N4), marks an important step toward the practical application of photocatalysis. Research advances show that a number of shortcomings still exist, such as less active sites, high charge recombination rates, and low visible light harvesting abilities. Such limitations have imposed severe restrictions on further applications of g-C3N4. As a result, considerable efforts are being devoted to enhancing the photocatalytic performance of pristine g-C3N4. This chapter begins with a detailed review of the recent progress in research on the modification of pristine carbon nitride for hydrogen evolution. Discussions on the morphology, copolymerization, doping, hybridization, and sensitization are provided. These discussions are followed by a brief introduction to the potential applications in another area, that is, energy storage using modified g-C3N4. Finally, promising perspectives on future research and application opportunities using carbon-based photocatalysts for energy are proposed.